Research and development from the bottom up - introduction of terminologies for new product development in emerging markets - Alexander Brem; Pierre Wolfram (Journal of Innovation and Entrepreneurship, 2014)
This paper gives a comprehensive overview of the commonly used terms jugaad, frugal innovation, frugal engineering, constraint-based innovation, Gandhian innovation, catalytic innovation, grassroots innovation, indigenous innovation, and reverse innovation. Based on that, a conceptual framework is introduced consisting of three core dimensions: sophistication, sustainability, and emerging market orientation. On the basis of these dimensions, analogies and distinctions between the terms are identified and general tendencies are explored such as the increasing importance of sustainability in social and ecological context or the growing interest of developed market firms in approaches from emerging markets. Hence, the presented framework supports further research in new paradigms for research and development (R&D) in developed market firms (DMFs), particularly in relation to emerging markets. This framework enables scholars to compare concepts from developed and emerging markets, to address studies specifically by using consistent terms, and to advance research into the concepts according their characterization.
Keywords: 650; Frugal innovation; Reverse innovation; Emerging economies; DMFs; R&D